Licensing Of SMEs Under Law Number 11 Of 2020 Concerning Work Creation Reviewed From Cost-Benefit Analysis - Kurniawan, Itok Dwi (JMB : Jurnal Manajemen dan Bisnis, 2024)
This research aims to find out two things, namely the amendments to the articles ofLaw Number 20 of 2008 concerning Micro, Small and Medium Enterprises (MSMEs) in Law Number 11 of 2020 concerning Job Creation, especially regarding the requirements for establishing MSMEs, as well as cost analysis andbenefits in comparison to Law Number 20 of 2008 concerning MSMEss and Law Number 11 of 2020 concerning Job Creation. The research design used is a normative legal research method, namely the comparison of legislation between Law Number 20 of 2008 concerning MSMEs and Law Number 11 of 2020 concerning Job Creation. The data analysis technique used is content analysis andcost and benefit analysis to determine the impact of the Job Creation Law on society. The Job Creation Law makes it easier for prospective MSMEs players and MSMEs entrepreneurs. MSME will get legality to facilitate tax administration, making it easier to get incentives. Based on the analysis of costs and benefits, the Job Creation Law can increase economic growth, increase the number of jobs, andincrease income. In contrast, the costs incurred include administrative costs,monitoring costs, risk control costs, conflict costs, and environmental damage costs. The Job Creation Law must provide a single database management status, especially regarding OSS for MSMEss, related to regulated data and its functions so that business actors can feel a positive impact